2017
DOI: 10.1055/s-0037-1603936
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Thrombotic Risk Assessment of Anti-β2 Glycoprotein I Domain I Antibodies: A Systematic Review

Abstract: We report an overall estimated median prevalence of anti-βGPI-DI antibodies of 44.3% in patients with APS and/or SLE and a significantly higher prevalence among patients with APS compared with SLE alone. Anti-βGPI-DI antibodies might represent a promising tool when assessing thrombotic risk in patients with APS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 42 publications
2
41
1
3
Order By: Relevance
“…Several different studies have shown a significant association of anti-D1 positivity to the risk of thrombosis, while the correlation with pregnancy morbidity was less evident [130][131][132][133][134].…”
Section: The Addition Of Anti-domain I To Laboratory Classification Cmentioning
confidence: 97%
See 3 more Smart Citations
“…Several different studies have shown a significant association of anti-D1 positivity to the risk of thrombosis, while the correlation with pregnancy morbidity was less evident [130][131][132][133][134].…”
Section: The Addition Of Anti-domain I To Laboratory Classification Cmentioning
confidence: 97%
“…Of the 25 potentially relevant publications, 15 studies have been selected for analysis. Pulling together the results of 11 papers, for a total of 1585 patients, the overall estimated median prevalence of anti-D1 antibodies was 43%, ranging from 26.7% in SLE patients to 55.4% in primary APS [130].…”
Section: Anti-β2gpi Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…13,14 Kelchtermans et al therefore provide an overview of studies on these antibodies and discuss their relevance for the pathophysiology of the syndrome, 15 and Radin et al summarize the available evidence to support their use in the diagnostic workup of patients in a systematic review. 16 How circulating aPL are linked to thrombosis and pregnancy-associated pathology remains a topic of investigation. Sacharidou et al therefore summarize the currently available data on the pathophysiology of APS.…”
mentioning
confidence: 99%